Persistent Postural-Perceptual Dizziness - Baužaitė, Ieva; Navickaitė, Viktorija; Vaitkus, Antanas (Neurologijos seminarai, 2024)
Persistent postural-perceptual dizziness (PPPD) is a common cause of dizziness and vertigo. This term was first described fairly recently by the International Classification of Vestibular Disorders in 2017. The symptoms include unsteadiness, vertigo or dizziness, lasting at least 15 days per month for 3 months or longer. The symptoms are exacerbated by upright posture, standing, walking or in the presence of various visual stimuli. The cause of this disorder is still unknown, although it is believed that it is related with the discoordination of the peripheral sensory and the central nervous systems. The onset of dizziness has been explained as the result of failure of integrating visual, vestibular and proprioreceptive signals into the central nervous system. The symptoms are often succeeding a previous vestibular disorder, e.g. vestibular neuronitis, benign paroxysmal positional vertigo (BPPV), Ménière’s disease or other disorders. Psychological factors also play a part in the onset of PPPD – patients quite frequently present a history of anxiety, neurotic tendencies and depression. PPPD diagnosis is clinical, a thorough anamnesis and clinical examination are crucial. In order to diagnose PPPD correctly, a set of all five criteria, established by the Bárány society, should be met. The treatment is usually multimodal, consisting of vestibular rehabilitation, cognitive behaviour therapy, selective serotonin reuptake inhibitors (SSRI) and serotonin norepinephrine reuptake inhibitors (SNRI).This review describes the term of PPPD, the symptoms of the disease, epidemiology, etiology, pathogenesis, comorbidities, also the diagnostic criteria and treatment of PPPD. The purpose of this article is to educate about this disease and to encourage more research, as well to seek better care for patients, accomplished by a multidisciplinary team of healthcare professionals.